Exploring the use of the 'Adapted Miracle Question' in the assessment of low back pain. - Nichols, V; Griffiths, F; McCarthy, C; Lamb, S (2011)
BACKGROUND: Low back pain is a complex condition, often recurring or chronic, which has proved difficult to characterise. To explore an alternative approach to assessing low back pain, an expert panel adapted the 'Miracle Question' from Solution-Focused Brief Therapy. This asks about a forward scenario of waking without the problems that the client had presented with. The question was adapted to: What would you do if you did not have back pain? OBJECTIVES: To explore the use of the Adapted Miracle Question (AMQ) within an interview study of patients with low back pain. DESIGN, SETTING AND PARTICIPANTS: The AMQ was used in an interview study of 34 participants recruited from the UK Back Skills Training (BeST) trial, assessing the effectiveness of a cognitive behavioural approach intervention for the management of low back pain. Responses to the AMQ were analysed thematically and then case by case. RESULTS: Interviewees talked about details of their activities and ability to function that would be different, and about change to their quality of life. Some talked about work. Five interviewees said that it would make no difference to them. When considered overall, the responses could be categorised as: no change; some change in activity/function; a return to their pre-back pain state; and life would be transformed. CONCLUSION: The AMQ was straightforward to ask and prompted a breadth of responses which may be useful in tailoring treatment. This question warrants further evaluation in the clinical setting.